Method of Calculating Effective Exchange Rates and Indicators of Competitiveness - Durand, Martine (OECD Economics Department Working Papers, 1986)
This paper describes the method of calculation of competitiveness indicators and effective exchange rates that are published half-yearly by the Secretariat in the Economic Outlook. This calculation is based on a double-weighting principle: the procedure calculates the relative importance of different countries on each market according to the relative importance of these markets for the country in question. The calculations include the impact of the domestic producer in each market, i.e. a particular country is considered as a competitor to other exporters to its own market. On the other hand, in calculating the importance of each competitor to a given country the share of the country in question is excluded in every market, i.e. a country cannot compete with itself. Weighting matrices have been constructed for each year, starting in 1970, and have been used to define and compute relative indices of costs, prices and exchange rates ...